Number of Metabolic Syndrome Risk Factors is Related to Carotid Intima-Media Thickness in Rheumatoid Arthritis Patients - Ferhat GÖKMEN; Ahmet TEMİZ and Ayla AKBAL and Hacer ŞEN and Coşkun ZATERİ and Esra GÖKMEN and Emre BOZKURT and Hatice REŞORLU and Tolga KURT and Yılmaz SAVAŞ (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the relationship between carotid intima-media thickness (CIMT) and clinical and metabolic variables in rheumatoid arthritis (RA) patients. Patients and methods: The study included 76 RA patients (18 males, 58 females; mean age 50.1±9.8 years; range 21 to 69 years) and 42 control subjects (11 males, 31 females; mean age 49.2±9.7; range 28 to 66 years). Erythrocyte sedimentation rate, C-reactive protein, and disease activity score were used to assess disease activation. Rheumatoid factor, anti-cyclic citrullinated peptide antibodies, and metabolic syndrome components (fasting blood glucose, high density lipoprotein-cholesterol, triglyceride, blood pressure, and waist circumference) were measured. Results: Mean disease duration was 6.9±6.5 years. Patients with RA had higher CIMT than the controls (0.8±0.1 and 0.6±0.2, respectively; p<0.001). Statistically significant positive correlations were observed between CIMT and age, erythrocyte sedimentation rate, C-reactive protein, and systolic and diastolic blood pressure. The CIMT in RA patients having metabolic syndrome risk components ranging from one to four were 0.76±0.16, 0.82±0.14, 0.86±0.13, and 0.92±0.13, respectively. CIMT was positively correlated with the number of metabolic syndrome risk components. Conclusion: Our study has shown elevated CIMT in RA. Presence of metabolic syndrome components in RA patients increases tendency to atherosclerosis and constitutes a severe risk for cardiovascular disease.